Prediction of paddy irrigation requirements by using statistical downscaling and cropwat models: A case study from the Kerian Irrigation Scheme in Malaysia - Hamidon N.; Harun S.; Malek M.A.; Ismail T.; Alias N. (Penerbit UTM Press, 2023)
With an average rainfall of 2500mm per year, Malaysia has abundant water resources but climate change coupled with drought, urbanisation and pollution sometimes causes water stress. Global warming has changed the local climate, threatening agricultural activities with particular impact on paddy production systems. To ensure availability of sufficient irrigation water for growing crops, there is a need to estimate future irrigation water requirements in the face of the complex dynamic resulting from global warming. The current study was therefore carried out to estimate paddy irrigation water requirements based on future climate trends by using SDSM and CROPWAT Models at the Kerian Irrigation Scheme, Perak, Malaysia. The application of the SDSM model revealed that both temperature and rainfall will increase in the future. Meanwhile the CROPWAT model predicted that the annual irrigation requirement will slightly decrease for period between 2010-2069 and increase for years 2070-2099 even though crop evapotranspiration (ETcrop) is predicted to increase in future for rise in temperature for year 2010 to 2099. This integration of SDSM and CROPWAT models produced better simulations of crop water requirement and irrigation requirement. Therefore, it can assist the reservoirs operating management team in giving effective and proficient response to climate changes in the future. 2015 Penerbit UTM Press. All rights reserved.